Production, antioxidant characterization and application of active starch-based films containing essential oils for beef packaging (Research, Society and Development, 2021)
The objective of this work was to study the antioxidant activity of biodegradable and active packaging containing essential oils. Seven types of active packaging were produced. In beef, lipid oxidation was measured using the thiobarbituric acid reactive substance test (TBARS); a microbiological analysis in beef was performed for Salmonella spp., coagulate positive Staphylococcus spp., Clostridium sulphite reducer and E. coli; the measurements were carried out on days 0, 3, 6, 9, 12 and 15 in triplicate. All packaging had exhibited antioxidant capacities and acted as an antioxidant in meat. The packages containing clove exhibited the highest total phenolic and antioxidant capacity (P < 0.05), and when used in beef were most effective against lipid oxidation. The use of oregano, clove and rosemary incorporated in active biodegradable starch based reduced microbial development and acted effectively against rancidity by maintaining the quality of meat stored under refrigerated conditions for 15 days.